First confirmed record of Scarus quoyi (Valenciennes, 1840) and Scarus zufar (Randall & Hoover, 1995) from the Gulf of Mannar, southeastern India - Rajathy, T. Jebarani; Mohanraj, T. (Zootaxa, 2026)
Parrotfishes (Family Scaridae) are keystone herbivores in coral reef ecosystems, regulating algal growth and facilitating coral recruitment through bioerosive feeding. We report the first confirmed records of Scarus quoyi (Valenciennes, 1840) and Scarus zufar (Randall & Hoover, 1995) from the Gulf of Mannar, southeastern India. Specimens (24.0 cm and 24.9 cm TL, respectively) were collected in April 2025 from artisanal fish traps operating at 10–15 m depth near Therespuram. Morphometric and meristic analyses confirmed species identity based on diagnostic features, including the characteristic dark green cheek blotch in S. quoyi and the yellow caudal base patch with irregular vertical bands in S. zufar. These records represent significant eastward range extensions: S. quoyi from the western Pacific into the Bay of Bengal, and S. zufar from its type locality in Oman through the Arabian Sea to India’s southeastern coast. The occurrence of S. zufar in mixed rocky-coral substrates may explain its previous absence from coral-focused surveys. These findings underscore the importance of continued systematic surveys and morphological documentation in biodiversity hotspots, particularly for taxonomically challenging groups exhibiting ontogenetic color variation.